Why Turkey? Afghans heartwarming migrating destination - Hakim, Abdul Ahad; Abdul Ghafoor Hatifie , (Technium Social Sciences Journal, 2020)
In the latest year, Turkey is the destination country for illegal Afghan migrants, as Directorate general of migration management of Turkey report shows that Afghanistan has a high number of the illegal migrants in Turkey in 2019. (7) This study concentrated to determine the factors associated with the area of destination (pulling factors), social demography of immigrants, income comparison, satisfaction, and re-integration of Afghan illegal migrants in Turkey in the last five years. The data collected by a well-structured questionnaire and applied to 384 illegal Afghan immigrants in Turkey (Istanbul, & Ankara) during June, 2019. The finding shows that Security 9.14, rights (women rights 8.52, human rights 8.43) and desire of having more regular life are the main reasons that attracts migrants. Dis-satisfaction of being in Turkey and being dis-agree to re-integrate back to Afghanistan is the finding of this research.